Russian literary culture in the camera age : the word as image - Hutchings, Stephen C. (London ; New York : RoutledgeCurzon, 2004)
"This book explores how one of the world's most literary-oriented societies entered the modern visual era, beginning with the advent of photography in the nineteenth century, focusing then on literature's role in helping to shape cinema as a tool of official totalitarian culture during the Soviet period, and concluding with an examination of post-Soviet Russia's encounter with global television. As well as pioneering the exploration of this important new area in Slavic Studies, the book illuminates aspects of cultural theory by investigating how the Russian case affects general notions of literature's fate within post-literate culture, the ramifications of communism's fall for media globalization, and the applicability of text/image models to problems of intercultural exchange"--Jacket
Russian realism and the camera : out from under Gogol's 'portrait' -- Objectivity, alienation and the fragmentation of the subject : the camera as midwife to modernity -- Photographic eye as poetic I : dialogues of text and image in Maiakovskii's and Rodchenko's Pro eto project -- The Stalinist ekranizatsiia as embodied word -- Shooting the canon : ekranizatsii and the (de)centring of Stalinist culture -- Metatextuality in the post-Stalinist ekranizatsiia : the official sphere unravels -- Hamlet with a guitar : the autobiographical persona of Vladimir Vysotskii as an intermedia phenomenon -- Literature as translation mechanism in post-Soviet televisual representations of Westernness -- In place of a conclusion : television, the end of literature and Pelevin's generation 'P'.
Includes bibliographical references (pages 187-220) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Russian literature -- History and criticism; Ekphrasis; Literature and photography; Motion pictures and literature; Television and literature; Littérature russe -- Histoire et critique; Ekphrasis; Littérature et photographie; Cinéma et littérature.; Télévision et littérature.; ekphrasis; LITERARY CRITICISM -- Russian & Former Soviet Union; Ekphrasis; Literature and photography; Motion pictures and literature; Russian literature; Television and literature; Russisch; Literatur; Wort; Fotografie; Electronic books; Criticism, interpretation, etc